Increasing income inequality: productivity, bargaining and skill-upgrading - Anders Frederiksen; Odile Poulsen (Institute for the Study of Labor (IZA), 2010)
In recent decades most developed countries have experienced an increase in income inequality. In this paper, we use an equilibrium search framework to shed additional light on what is causing an income distribution to change. The major benefit of the model is that it can accommodate shocks to the skill composition in the market, employee bargaining power and productivity. Further, when our model is subjected to skill-upgrading and changes in employee bargaining power, it is capable of predicting the recent changes observed in the Danish income distribution. In addition, the model emphasizes that shocks to the employees' relative productivity, i.e., skill-biased technological change, are unlikely to have caused the increase in income inequality.
Keywords: J3; J6; M5; 330; Income inequality; two-sector search model; bargaining power; skill-biased technological change; Einkommensverteilung; Verteilungstheorie; Mehr-Sektoren-Modell; Arbeitsmarkttheorie; Arbeitsuche; Suchtheorie; Schock; Qualifikation; Technischer Fortschritt; Arbeitsproduktivität; Lohnverhandlungen; Verhandlungsmacht; Theorie; Dänemark